Multidimensional cognitive ability, intermediate channels, and financial outcomes - Ștefania Simion; Tomasz Sulka (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
In this paper, we examine which dimensions of cognitive ability are most predictive of key financial outcomes and what pathways could account for the observed relationships. We begin by proposing a conceptual framework that accounts for several plausible "channels" through which differences in cognitive ability might influence financial outcomes. Subsequently, we put the framework to test using the English Longitudinal Study of Ageing. We find that numeracy and literacy are strong predictors of different measures of wealth level and composition, after controlling for a rich set of demographic characteristics. We also find that our end-node channels, planning and self-control, have an even greater predictive power. Nevertheless, despite the fact that these channels are strongly correlated with both numeracy and literacy, they do not fully account for the pathways from cognitive ability to financial outcomes.
Keywords: C13; D91; J14; J24; 330; Cognitive Ability; Numeracy; Financial Literacy; Planning; Self-Control